Systematic pan-cancer analysis identifies PKNOX1 as a potential prognostic and immunological biomarker and its functional validation - Liu, Kan; Xu, Yongkang; Mao, Ye; Fu, Shumin; Huang, Shenglan; Wu, Jianbing (Frontiers in Immunology, 2025)
BackgroundPBX/knotted1 homeobox 1 (PKNOX1), also known as PREP1, is a homeodomain transcription factor that has been reported to be involved in the progression of gastric adenocarcinoma and non-small cell lung cancer. However, its expression, clinical significance, and biological function in various human cancers have not been studied in depth, and its role and specific molecular mechanism in the occurrence and development of cancer remain unclear. Its potential as a cancer prognostic marker and therapeutic target has not yet been explored.MethodsThe TCGA and GTEx databases were used to evaluate the differential expression of PKNOX1 pan-cancer, and PKNOX1 gene mutation information was obtained from the cBioPortal and GSCALite platforms. Cox regression and Kaplan-Meier analyses were used to evaluate the value of PKNOX1 in pan-cancer prognosis. The correlations between PKNOX1 expression and the expression of DNA methylation-related genes, immune-related genes, tumor mutation burden (TMB), and microsatellite instability (MSI) were analyzed using Spearman correlation. The correlations between PKNOX1 expression and MDSC immune infiltration and immune cells were analyzed using the TIDE algorithm and the ESTIMATE algorithm. PKNOX1 -interacting proteins and expression-related genes were analysed via the STRING and TIMER 2.0 platforms, and the functions of PKNOX1 in tumors and the cell pathways involved were predicted via KEGG enrichment analysis. In addition, the differential expression and function of PKNOX1 in HCC and breast cancer were explored via Western blotting and proliferation and migration-related experiments.ResultsPKNOX1 is significantly highly expressed in most tumor types and is significantly associated with poor patient prognosis and increased clinicopathological stage. Tumor gene mutations and DNA methylation may explain the abnormal expression of PKNOX1. In most tumors, PKNOX1 expression was significantly correlated with MDSC immune infiltration and immune cells, methylation-related genes, immune-related genes, the TMB and MSI. The enriched KEGG pathways indicated that PKNOX1 is involved in cancer-promoting processes such as cell-cell adhesion, the cell cycle and cell proliferation and deterioration signalling pathways. In vitro experiments revealed that PKNOX1 is highly expressed in HCC and breast cancer cells and HCC tissues and promotes the growth, proliferation, migration and invasion of HCC and breast cancer cells.ConclusionPKNOX1 is a promising prognostic and immune biomarker in pan-cancer and may play an important role in HCC and breast cancer progression and metastasis.